Paulus und Barnabas in der Provinz Galatien: Studien zu Apostelgeschichte 13f; 16,6; 18,23 und den Adressaten des Galaterbriefes - Breytenbach, Cilliers (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1996)
This study poses and answers two questions: 1. What is the basis in the tradition for the Acts 13 and 14 narrative about Paul's and Barnabas' mission on Cyprus and in southern Galatia? 2. Who are the addressees of the letter to the Galatians? Using the extant inscriptions and literary sources that relate to the provinces of Cyprus and Galatia in the early Roman Empire, the above questions are addressed to Acts and Galatians, and answered as follows: 1 Acts 13-14 contains so much local colour as to rule out the thesis that the so-called first missionary journey is fictional. 2. Paul's letter to the Galatians is addressed to the churches in southern Galatia - Antioch, Iconium, Lystra and Derbe. The hypothesis of a north-Galatian setting is shown to be improbable in the light of the geographical, archaeological and epigraphic evidence.